2015
DOI: 10.1016/j.devcel.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroid Signaling Regulates Leaf Erectness in Oryza sativa via the Control of a Specific U-Type Cyclin and Cell Proliferation

Abstract: Leaf erectness is key in determining plant architecture and yield, particularly in cereal crops. Brassinosteroids (BRs) play a unique role in controlling this trait in monocots, but the underlying cellular and molecular mechanisms remain big mysteries. Here we report that the abaxial sclerenchyma cell number of rice lamina joints (LJs) is closely related to leaf erectness, and BR signaling tightly regulates their proliferation. We identified a rice U-type cyclin CYC U4;1 enriched in rice LJs, with its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 44 publications
7
110
0
Order By: Relevance
“…5A). Consistent with the finding that OsCycU4;1 is involved in cell division at the abaxial side during lamina joint development (Sun et al, 2015), OsCycU2;1 and OsCycU4;1 are highly expressed in the lamina joint with C1 and C2 patterns, while OsCycD5;2 is lowly expressed, indicating a distinct regulatory mechanism. Interactions with cyclins and protein phosphorylation are important for CDK activity.…”
Section: Drastic Expression Changes Of Cell Division/expansionrelatedsupporting
confidence: 74%
See 4 more Smart Citations
“…5A). Consistent with the finding that OsCycU4;1 is involved in cell division at the abaxial side during lamina joint development (Sun et al, 2015), OsCycU2;1 and OsCycU4;1 are highly expressed in the lamina joint with C1 and C2 patterns, while OsCycD5;2 is lowly expressed, indicating a distinct regulatory mechanism. Interactions with cyclins and protein phosphorylation are important for CDK activity.…”
Section: Drastic Expression Changes Of Cell Division/expansionrelatedsupporting
confidence: 74%
“…On the other hand, transgenic rice plants overexpressing sterol C-22 hydroxylase (an important enzyme of BR biosynthesis; Wu et al, 2008), OsDim/dwf1 (which participates in late steps of sterol biosynthesis; Hong et al, 2005), and OsBAK1 ) present increased leaf inclination, which is consistent with BR promoting cell elongation at the adaxial side of the lamina joint (Cao and Chen, 1995). A recent study showed that BR signaling inhibits the proliferation of sclerenchyma cells at the abaxial side of the lamina joint by coordinately regulating the U-type cyclin CYCU4;1 (Sun et al, 2015).…”
mentioning
confidence: 50%
See 3 more Smart Citations